Compatibility of Hydroxyethyl Starch and Tranexamic Acid for Battlefield Co-Administration. Issue 10 (1st October 2016) - Studer, Nicholas M.; Yassin, Ahmad H.; Keen, Donald E.
ABSTRACT: Introduction: The current Tactical Combat Casualty Care Guidelines recommend tranexamic acid (TXA) administration for casualties in whom massive blood transfusion is anticipated. However, despite Hextend being the recommended resuscitation fluid, the guidelines recommend against using TXA with Hextend. This appears to be due to a concern about pharmaceutical compatibility, despite the absence of a direct study of compatibility in the literature. Methods: Two solutions of Hextend and TXA were examined for compatibility. One solution simulated direct Y-site injection of TXA, and a second solution replicated a typical piggyback infusion. These solutions, along with two control solutions, were observed for the formation of precipitants immediately on mixing, at 1 hour, and at 4 hours by unaided visual inspection, as well as with the use of a basic digital turbidimeter. Results: No evidence of chemical or physical interaction was noted by visual inspection at any time in either solution. In addition, turbidimeter results did not demonstrate a difference of greater than 10% from the control solutions, falling below the cutoff set in other studies as an indicator for precipitant formation. Conclusion: There was no evidence of incompatibility between the solutions of Hextend and TXA by either visual inspection or by digital turbidimeter.